Carotid-compression Technique for the Insertion of Guiding Catheters - Yoshimura, S. (AJNR Am J Neuroradiol, 2006)
SUMMARY: Inserting a guiding catheter into a tortuous artery for neurointerventional procedures can be difficult. In our technique, the carotid artery is manually compressed to stabilize and/or straighten the inserted wire before advancing the guiding catheter. Although this technique is not risk-free and care must be taken to avoid vascular injury by excessive compression, it is useful for the insertion of a guiding catheter into the carotid artery.